The boys in the boat : nine Americans and their epic quest for gold at the 1936 Berlin Olympics - Brown, Daniel, 1951- (Viking, 2013)
Tells how in 1936 the University of Washington's eight-oar crew, composed of the sons of loggers, shipyard workers, and farmers who had mastered collegiate rowing, went on to the Berlin Olympics where they defeated Adolf Hitler's German team to achieve the Olympic gold medal.